The Effect of Torbangun (Coleus amboinicus Lour) Leaf Extract on Antibiotic Resistant Bacteria Escherichia coli pBR322 and Toxicity Tests on Artemia salina Leach - Suryowati, Trini; Yang, John Jackson; Sunarti, Lusia Sri; Bintang, Maria (Indonesian Journal of Applied Research (IJAR), 2024)
Inappropriate antibiotic use can lead to antibiotic resistance, causing many problems in the treatment of Escherichia coli infection. One way to avoid resistance is to use the traditional medicine Coleus amboinicus Lour, also known as Torbangun in Indonesia. The purpose of this study was to determine the inhibitory ability of 70% ethanol extract of Torbngun leaf against Escherichia coli pBR322 has plasmid pBR322, which is resistant to antibiotics Ampicillin and Tetracycline based on activity and minimum inhibitory concentration. Extraction was carried out using the maceration method. The presence of inhibition zones indicated antibacterial activity. The appearance of the inhibition zone at the minimum concentration indicated the minimum inhibitory concentration. Following this, the cytotoxic activity was evaluated using the brine shrimp lethality test. Data analysis was performed using an unpaired t-test using GraphPad Prism® software. Antibacterial activity tests showed that a 15% torbangun leaf extract concentration had inhibitory power against Escherichia coli pBR322. The toxicity test of torbangun leaf extract against Artemia salina Leach shrimp larvae showed LD50 results at a concentration of 150 ppm.